THE INFLUENCE OF ORGANIZATION COMMITMENT AND COMPENSATION ON EMPLOYEE PERFORMANCE MEDIATED BY ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Mercy Melinda Putri; Anis Siti Hartati; Agus Haryadi (Jurnal Ekonomi dan Bisnis Airlangga, 2021)
Introduction: The purpose of this study is to describe and explain the influence between variables of Organizational Commitment, Compensation, Organizational Citizenship Behavior (OCB), and Employee Performance.Methods: This study includes quantitative and descriptive research. The sample in the study amounted to 50 employees taken using a saturated sampling technique. The data obtained are analyzed using path analysis.Results: The results of this study prove that there is a direct significant influence of organizational commitment and compensation on employee performance. In addition, the results of this study also prove that there is no indirect influence of organizational commitment on employee performance mediated by OCB and there is an indirect influence of compensation on employee performance mediated by OCB.Conclusion and suggestion: The company should focus more on increasing the direct influence of organizational commitment on employee performance.